Brain-based learning and high order thinking skills effect on students’ writing ability - Zuhriyah, Mukminatus; Agustina, Ria Kamilah (JEES (Journal of English Educators Society), 2020)
In this study, the researchers implemented brain-based learning (BBL) model and the use of the students’ high order thinking skills (HOTS) in the teaching and learning of writing. The aim of this study was to know whether or not there was an interaction effect between teaching models and students’ HOTS on the students’ writing ability. This experimental research used a 2x2 factorial design. Two classes of the fourth semester of English Language Department became the population and the sample in this study. The students in both of the classes were divided into the students with high and low HOTS. Then, the experimental class was taught writing by using BBL and the control class used guided writing. Next, the data got from the writing test were calculated by using a two-way ANOVA. The result showed that Fo interaction (10.160) was higher than Ft (4.15) at the level of significance α=0.05. It means that there was an interaction effect between teaching models and students’ HOTS on the students’ writing ability. The mean score of the students with high HOTS taught by using BBL (82.44) was the highest. This brings to the conclusion that BBL and HOTS had significant interaction effect on the students’ writing ability. The skills of analyzing, evaluating and creating the students whose HOTS was high worked well when having discussion. The students’ relaxed feelings in BBL class could help them to get information about what to be written in their texts more and more by having discussion.